An Assessment of the Health Implications of Poor Household Toilets on the Population in Bomaka, Buea Municipality, Fako Division, South West Cameroon - Anumveh, Nkemasong Nicasius; Nkuh, Yinkfu Randy; Mojoko, Mbella Fiona; Amos, Fang; Malu, Nformi Beatrice; Adamu, Baba (International Journal of Global Sustainability, 2022)
Household latrines remain one of the most vital aspects of housing facilities neglected in housing development in fast growing urban peripheral zones. The existence of dilapidated latrines has become the new normal in the Bomaka locality and with the associated health consequences. This study sought to investigate the implications of poor household latrines (independent variable) in the Bomaka locality on the health conditions of the inhabitants (dependent variable). The study employed the mixed research design (triangulation) combining the observational and exploratory methods with emphasis on both quantitative and qualitative techniques. Field observations, questionnaires administration, interviews and focused group discussions were the primary data sources while consultation of online and offline documents and the data bases of health facilities were secondary sources of data. The target population was all the households and their toilets stratified into three neighbourhoods following the high priority streets namely the Chief, Kawah and Miss Bright Streets. The population was stratified into classes based on their education, income and occupational status. Through the multistage sampling procedure of stratified random sampling, a total of 150 individuals were selected as respondents. Both descriptive (percentiles) and inferential (correlation analysis) statistical tool were used to process the data to establish the results. Results revealed that majority (69.5%) of the inhabitants owned household latrines with the bulk being outdoor pit toilets (79.5%) followed by external water closets (8.5%). Furthermore, most of the toilets were constructed with plank material (53.3%) with up to 20% of the toilets being open air (unconstructed). A high proportion (67.2%) of the toilets are very poorly constructed and also the man-toilet ratio is very high thereby creating much inconveniences during rush hour periods (mornings and evening). It was established that the dismal toilet facilities have induced significant health problems with the prevalence of infectious diseases dominated by intestinal diseases (56.4%) as diarrhoea, dysentery and cholera, which are suffered by 3 persons out of every 10 members of the households. Individuals do adapt to the challenges of poor latrines by defecating in nearby bushy areas and streams, and also in plastic bags for disposal later. This leads to the constant pollution of our water sources and food. This work recommends that the Bomaka locality offers many livelihood options to its population and therefore, adequate sensitisation campaigns, better toilet infrastructural development should be carried out to enhance the level of sanitation and well-being of individual in the locality. Also, regular inspection tours by council hygiene and sanitation department and support NGOs stand out as vital solutions to redress this worsening situation.